The management of hypocalcaemia in UK dairy herds - Garnett, Eleanor J M (2017)
Periparturient milk fever is a widespread metabolic disease within the dairy industry, with a number of potential impacts on the affected animals’ health and productivity in the subsequent lactation that can have a considerable economic impact on farmers. This thesis aimed to investigate current attitudes of both UK dairy farmers and veterinarians towards milk fever and subclinical hypocalcaemia, as well as investigating the feeding of rumen-protected rice bran during the dry period as a milk fever preventative, due to its reported potential as a calcium binder, within a commercial UK dairy herd. A retrospective study was also carried out in order to investigate associations between recorded milk fever events and other outcomes from farm records obtained from 78 UK dairy herds. The levels of agreement between three different blood sample types (serum, lithium heparin plasma, and lithium heparin whole blood) were also considered with regard to testing for concentrations of calcium, magnesium and phosphorous. Questionnaires were distributed to UK dairy farmers and veterinarians in order to assess current attitudes towards milk fever and its prevention. When choosing a prevention strategy, farmers were most concerned with its efficacy, with its ease of use being their second priority. Veterinarians placed a greater importance on metabolic disease than farmers, and it appears that vets may have an important role in education on the subject of hypocalcaemia.